PERAN SOSIALISASI PAJAK DALAM MEMODERASI LITERASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA MAKASSAR - Rezky Ramadhani Aras, Amalia; Mappatompo, Andi; Amran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of tax literacy on the compliance of MSME taxpayers in Makassar City, with tax socialization as a moderating variable. MSMEs play a significant role in Indonesia's economy, contributing over 60% of GDP and absorbing more than 97% of the workforce. However, MSME taxpayer compliance in Makassar remains below 70% of registered taxpayers. This research uses a quantitative approach with an associative causal design. Data were collected through questionnaires distributed to 100 MSME respondents selected using purposive sampling from those registered under the Makassar City Cooperative and MSME Office. Data analysis was conducted using Moderated Regression Analysis (MRA) with SPSS software. The results show that tax literacy has a significant positive effect on taxpayer compliance (t-value = 3.709 > t-table = 1.985; sig. = 0.001). Tax socialization also positively and significantly affects compliance (t-value = 2.159 > t-table = 1.985; sig. = 0.002). Furthermore, tax socialization significantly strengthens the effect of tax literacy on compliance (t-value = 3.393 > t-table = 1.985; sig. = 0.001), categorized as quasi moderation because it functions both as an independent variable and a moderating variable. The coefficient of determination (R²) reaches 0.853, meaning the model explains 85.3% of variance in taxpayer compliance. These findings emphasize the importance of enhancing tax literacy supported by effective socialization programs to encourage consistent MSME taxpayer compliance.